2010
DOI: 10.1124/jpet.109.162032
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Transmembrane Regulator Inhibitors CFTRinh-172 and GlyH-101 Target Mitochondrial Functions, Independently of Chloride Channel Inhibition

Abstract: Two highly potent and selective cystic fibrosis (CF) transmembrane regulator (CFTR) inhibitors have been identified by high-throughput screening: the thiazolidinone CFTR inh -172 [3-[(3-trifluoromethyl)phenyl]-5-[(4-carboxyphenyl)methylene]-2-thioxo-4-thiazolidinone] and the glycine hydrazide GlyH-101 [N-(2-naphthalenyl)-((3,5-dibromo-2,4-dihydroxyphenyl)methylene)glycine hydrazide]. Inhibition of the CFTR chloride channel by these compounds has been suggested to be of pharmacological interest in the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 41 publications
3
57
1
Order By: Relevance
“…CFTR inh -172 does not function as an open channel blocker since there is no rectification of current during block (32). Several different mechanisms of block have been proposed (24,27). For GlyH-101, no site-directed mutagenesis studies have been performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CFTR inh -172 does not function as an open channel blocker since there is no rectification of current during block (32). Several different mechanisms of block have been proposed (24,27). For GlyH-101, no site-directed mutagenesis studies have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…CFTR inh -172 inhibits sodium transport in sweat glands (62). Both CFTR inh -172 and GlyH-101 affect mitochondrial function, independent of their action on CFTR (24).…”
mentioning
confidence: 99%
“…In spite of the fact that short-time CFTR-unrelated effects of CFTR inh-172 have been described in CFTR lacking HeLa cells, 48 We also investigated the effects of CFTR depletion on EGF-induced trafficking of the EGFR. In 16HBE14o-cells transfected with scrambled siRNAs, EGF (and its receptor) was efficiently degraded after 30 and 60 min of stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…These data are consistent with our previous studies showing that inhibition of CFTR with CFTR inh -172 was sufficient to inhibit Nrf2 activity and thereby increase oxidant-mediated elevations in cytokine levels (7). Recently, Kelly and colleagues (14) concluded that increases in oxidants and inflammatory signaling in CF cell are independent of CFTR channel function loss, as CFTR inh -172 elicited these changes in cells that lack detectable levels of CFTR. However, these studies did show elevated levels of intracellular oxidants in the absence of CFTR inh -172 in CF vs. non-CF controls.…”
Section: Discussionmentioning
confidence: 99%